PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH MATEMATIS SISWA SMK MELALUI PEMBELAJARAN BERBASIS MASALAH - Faridah . Rangkuti; Sahat . Saragih; Hasratuddin . . (Study Program of Mathematics Education of Unimed Postgraduate Program, 2014)
ABSTRACTThe purpose of this research were to examine 1) differences in understanding the concept of capacity building of students who received problem-based learning with students who earn ordinary learning, 2) differences in the increase in mathematical problem solving ability of students who received problem-based learning with students who earn ordinary learning, (3) interaction between learning contributes to enhancing the ability of understanding the concept of the student, (4) the interaction between learning contributes to enhancing students' mathematical problem solving abilities, (5) the completion of the problems associated with the ability of understanding mathematical concepts and problem solving.This study was a semi-experimental study. The study population was a class XI student of SMK Negeri 1 Langsa. Of class XI were selected randomly two classes namely class XI and class XI AK1 AK2. XIAK2 grade students (the experimental class) treated the problem-based learning (PBM) and XIAK1 grade students (control group) treated with normal learning. The instrument used consists of: testing the ability of understanding concepts and problem solving ability test. Data analysis was performed with t-test and ANOVA two lanes.The results of this study were (1) increase the ability of students who are given the understanding of the concept of problem-based learning is higher than students who were given the usual learning (2) increase students' mathematical problem solving ability are given higher problem-based learning than students who were given the usual learning, (3) there was an interaction between gender and students 'learning abilities increase understanding of concepts, (4) there was an interaction between gender learning with students' mathematical problem solving abilities increase, (5) the completion of the students in problem solving abilities and understanding of the concept mathematical problem solving in problem-based learning is better than learning ordinary. The findings of the study recommend that the problem-based learning (PBM) can be used as an alternative learning models used in primary schools to achieve a high level of competence think.Keywords : problem-based learning, ability of understanding mathematical concepts, mathematical problem solving ability. ABSTRAKTujuan penelitian ini adalah untuk menelaah (1) perbedaan peningkatan kemampuan pemahaman konsep siswa yang memperoleh pembelajaran berbasis masalah dengan siswa yang memperoleh pembelajaran biasa, (2) perbedaan peningkatan kemampuan pemecahan masalah matematis siswa yang memperoleh pembelajaran berbasis masalah dengan siswa yang memperoleh pembelajaran biasa, (3) interaksi antara pembelajaran dengan gender terhadap peningkatan kemampuan pemahaman konsep siswa, (4) interaksi antara pembelajaran dengan gender terhadap peningkatan kemampuan pemecahan masalah matematis siswa, (5) proses penyelesaian soal-soal yang terkait dengan kemampuan pemahaman konsep dan pemecahan masalah matematis.Penelitian ini merupakan penelitian semi eksperimen. Populasi penelitian ini adalah siswa kelas XI SMK Negeri 1 Langsa. Dari kelas XI tersebut dipilih secara acak dua kelas yaitu kelas XI AK1 dan kelas XI AK2. Siswa kelas XIAK2 (kelas eksperimen) diberi perlakuan pembelajaran berbasis masalah (PBM) dan siswa kelas XIAK1 (kelas kontrol) diberi perlakuan pembelajaran biasa. Instrumen yang digunakan terdiri dari: tes kemampuan pemahaman konsep dan tes kemampuan pemecahan masalah. Analisis data dilakukan dengan uji t dan anava dua jalur.Hasil penelitian ini adalah (1) peningkatan kemampuan pemahaman konsep siswa yang diberi pembelajaran berbasis masalah lebih tinggi daripada siswa yang diberi pembelajaran biasa , (2) peningkatan kemampuan pemecahan masalah matematis siswa yang diberi pembelajaran berbasis masalah lebih tinggi daripada siswa yang diberi pembelajaran biasa (3) terdapat interaksi antara pembelajaran dengan gender siswa terhadap peningkatan kemampuan pemahaman konsep,(4) terdapat interaksi antara pembelajaran dengan gender siswa terhadap peningkatan kemampuan pemecahan masalah matematis, (5) proses penyelesaian siswa dalam menyelesaikan masalah kemampuan pemahaman konsep dan pemecahan masalah matematis pada pembelajaran berbasis masalah adalah lebih baik dibanding dengan pembelajaran biasa. Temuan penelitian merekomendasikan bahwa pembelajaran berbasis masalah (PBM) dapat dijadikan salah satu alternatif model pembelajaran yang digunakan di sekolah utamanya untuk mencapai kompetensi berpikir tingkat tinggi.Kata Kunci : pembelajaran berbasis masalah, kemampuan pemahaman konsep, kemampuan pemecahan masalah matematis